2017
DOI: 10.1155/2017/5839491
|View full text |Cite
|
Sign up to set email alerts
|

Open Approach to Primary Lumbar Hernia Repair: A Lucid Option

Abstract: Background Lumbar hernia is a rare type of hernia. Awareness of the anatomical basis of this hernia is important for proper diagnosis and treatment. Introduction Lumbar hernia is a protrusion of either extraperitoneal fat or intraperitoneal contents through either of the lumbar triangles. Primary lumbar hernias are extremely rare thereby rendering such a case reportable, to create an awareness about this condition to upcoming surgeons. Case Report A case of primary lumbar hernia treated successfully by open me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
(15 reference statements)
0
8
0
Order By: Relevance
“…Surgery was done in 4 cases, of which opened hernioplasty was done in three and was not mentioned in one. In a study done by Vagholkar et al, an open approach was implemented [23], similar to the method done in our study. They concluded that both laparoscopic and open approaches could be done, although open mesh repair is an easier, safer, and more effective method of treating this uncommon surgical illness [23].…”
Section: Discussionmentioning
confidence: 99%
“…Surgery was done in 4 cases, of which opened hernioplasty was done in three and was not mentioned in one. In a study done by Vagholkar et al, an open approach was implemented [23], similar to the method done in our study. They concluded that both laparoscopic and open approaches could be done, although open mesh repair is an easier, safer, and more effective method of treating this uncommon surgical illness [23].…”
Section: Discussionmentioning
confidence: 99%
“…While increased intra-abdominal pressure is considered a high-risk factor for all hernias, our patient reported heavy object lifting and had chronic obstructive pulmonary disease. A lumbar hernia may contain different intraperitoneal organs or extra peritoneal fat [3,7,9].…”
Section: Discussionmentioning
confidence: 99%
“…The IU (Petit’s) triangle is bordered medially by the latissimus dorsi muscle, laterally by the external oblique, and inferiorly by the iliac crest. The lumbodorsal fascia forms the floor of IU as it extends from the aponeuroses related to the transversus abdominis and the internal oblique (Figure 4) [2,7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An inferior lumbar hernia is a protrusion of either extraperitoneal fat or intraperitoneal contents through the inferior lumbar triangle. 2 The inferior lumbar triangle is anatomically defined by the iliac crest inferiorly, the external oblique muscle anteriorly, and the latissimus dorsi muscle posteriorly.…”
Section: Introductionmentioning
confidence: 99%